Study of dendritic growth of zinc crystals on the edges of steel sheet - Bengoa, Leandro Nicolás (2014)
In this paper, the formation of zinc dendrites at the strip edge of an industrial electrogalvanizing line was studied. For that purpose, a rotating washer electrode was designed to reproduce the hydrodynamic conditions and the current density distribution found in the industrial process. Polarization curves were recorded at different rotation speeds in order to investigate the electrokinetic behavior of the cathodic process. The induction time for dendritic growth was estimated for different overpotential values and the existence of a minimum overpotential below which dendrites do not grow was confirmed. Dendrite precursors on the edge of the washers were well characterized and its birth and precise location were studied. The general model of disperse and dendritic metal electrodeposit formation derived by Popov et al. was used to explain the effect of electrolyte zinc concentration, rotation speed of the cathode, electrolyte temperature and edge roughness on the size and morphology of dendrites. The results showed that this theory provides an accurate description of the phenomenon even for non-stationary electrodes, which have not been extensively studied so far. The experimental setup proved to be a powerful means to study the formation of dendritic growth of zinc crystals on the edges of steel strip and is well suited to characterize other metals that produce this type of defect.